Speech by the hon'ble Minister Of Agriculture and Fisheries,Tan Sri Datuk Haji Mohd Ghazali Bin Haji Jawi at the Annual Meeting Of The Asean Permanent Committee On Food And Agriculture on 25th September 1972 at 9.00 am to be held in conference room no.1 Parliament House ,Kuala Lumpur. - Jawi, Mohd Ghazali (1972)
On behalf of the goverment and people of Malaysia,it is indeed my pleasure to welcome you to this annual meeting of the Asean Permanent Committee On Food And Agriculture.